Nilai-Nilai Hadist Sebagai Dasar Pengembangan UMKM: Peluang dan Tantangan di Era Modern - Hidayat Hidayat; Wahyu Febri Ramadhan Sudirman; Muhammad Zaim (Global Sustainability Research Institute, 2024)
Introduction: This article aims to provide a better understanding of the Opportunities and Challenges in Micro, Small and Medium Enterprises Development with a hadith perspective a pproach. Methods: This research is a descriptive qualitative research using a literature research approach. The data sources in this research are primary and secondary data sources. primary and secondary data sources. Data collection techniques with keyword searches, subject searches and from recent scientific articles. from recent scientific articles. Results: Report the main result/findings is that the lack and lack of ability to read opportunities is a weak point in the development of Micro, Small and Medium Enterprises. In addition, marketing strategies, networking and promotion systems and funding often make Micro, Small and Medium Enterprises unable to compete in the distribution of their products in the market. So the research is expected to provide further policy recommendations to increase the strength of Micro, Small and Medium Enterprises as an opportunity and empower Micro, Small and Medium Enterprises in facing various challenges. Conclusion and suggestion: This article highlights the importance of research and a deeper understanding of the Opportunities and Challenges of Micro, Small and Medium Enterprises Development in Hadith Perspective. Along with the times, Micro, Small and Medium Enterprises are the main support in the country's economic growth, but along with its development there are many challenges in its development such as human resources, inability to monitor and lack of management knowledge and funding. This activity is a business that is in line with the teachings of Islam which is recommended in terms of buying and selling that is good and in accordance with Islamic religious law.